Abrasion of Pro Seal and Opal Seal by professional tooth cleaning protocols: results from an in vitro study and a randomized controlled trial - Deurer, Nadine; Erber, Ralf; Orhan, Gül; Zingler, Sebastian; Lux, Christopher J.; Şen, Sinan (European journal of orthodontics, 2020)
SummaryBackground. The integrity of orthodontic surface sealants after professional tooth cleaning (PTC) has previously only been evaluated in vitro. Recently
Advance access publication 25 November 2019
Gesehen am 11.02.2021